Workforce ecosystems reaching strategic goals with people, partners, and technologies - Altman, Elizabeth J.; Kiron, David; Schwartz, Jeff 1958-; Jones, Robin (The MIT Press, 2023)
"A practical guide for business leaders to manage workers within and outside their organizations."
Keywords: Strategisches Management / (DE-627)091393116 / (DE-2867)18029-0; Shareholder Value / (DE-627)091389283 / (DE-2867)19102-4; Labor supply / Management; Strategic planning